DINAMIKA PERUBAHAN KEBIJAKAN POLITIK DI ERA DIGITAL - lestari, reni puji; yohanes, yulius; noviana, kariana; kurniati, grace; juniarti, nengsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This article examines changes in political policy in the digital age, influenced by information and communication technology in decision-making. In an era of globalization and more open access to information, political policies have become clearer and more accountable. However, new challenges have emerged, such as the spread of misinformation and divisions in public opinion. Through case analysis and existing data, this article investigates how political parties and governments adapt to these changes and how this impacts public participation. The research findings indicate that policies responsive to needs in the digital world can enhance public participation and strengthen democracy.